USING VOA NEWS TOWARDS THE LISTENING SKILL OF THE SECOND GRADE STUDENTS OF MAN 2 MAKASSAR (International Conference on Social and Islamic Studies, 2021)
There are many medias can be used in teaching listening skills. VOA News is one of the best media that can make the students’ comprehend the content of listening material. In this study, researchers conduct the research with 2 classes. This research was aimed to examine whether or not the use of VOA News in teaching listening skill can affect the students’ listening skill at the second grade students. The research design used in this research was Quasi-experimental design with non-equivalent controlled group design. The technique used in taking the sample was purposive sampling. Data were collected by using instrument with pre-test and post-test. To get the result, the score of pre-test and post-test was analyzed by using a software called SPSS program. The first step in analyzed the data was normality test to know that the sample has been drawn from a normally distributed population. The second step was paired t-test to calculate the mean score, standard deviation, score of t-count and significant (2-tailed). The results showed that the null hypothesis was rejected which VOA News is not effective to increase the students listening skill while the alternative hypothesis was accepted which VOA News is effective to increase the students listening skill.